PERSPEKTIF HUKUM TERHADAP LATAR BELAKANG PENDIDIKAN ANGGOTA DPR - Tengku Indira Larasati; Hesti Yulianti (Lembaga Penelitian dan Pengabdian kepada Masyarakat STIH Awang Long, 2025)
According to Law Number 7 of 2023 concerning the Stipulation of Government Regulation in lieu of Law Number 1 of 2022 concerning Amendments to Law Number 7 of 2017 concerning General Elections into Law, a candidate for the House of Representatives must have completed senior high school or its equivalent. A key component of Indonesia's constitutional framework is the DPR. Considering the significance of the DPR's function within Indonesia's constitutional framework, the aforementioned minimal educational prerequisites must be revised. Normative legal research is the methodology employed. Legal literary research, or normative legal research, is legal research that uses literature as its primary source. In this research, the research approach is descriptive and analytical, meaning that the researcher will provide a comprehensive, systematic, accurate, and factual explanation of the facts found in the research object and then correlate them with relevant legal theories. Primary and secondary data are among the data types. By characterizing the data collected using legal norms, theories, and pertinent legal doctrines and regulations, the normative qualitative technique of data analysis was employed in this study. According to research findings, in order to create leaders and/or representatives with superior skills and capacities, it is imperative to change the prerequisites for joining the House of Representatives, particularly the minimal educational requirements for candidates. The quality of the legislative body's constitutional duties is directly impacted by the low educational backgrounds of House of Representatives (DPR) members. A lack of assured protection of people' constitutional rights, poor argumentation in the formulation of laws, and multi-interpretable legal norms are only a few of the issues that might arise when the majority of DPR members lack formal education.